2017
DOI: 10.1016/j.knosys.2017.01.028
|View full text |Cite
|
Sign up to set email alerts
|

ALGA: Adaptive lexicon learning using genetic algorithm for sentiment analysis of microblogs

Abstract: Sentiment analysis is about classifying opinions expressed in text. The aim of this study is to improve polarity classification of sentiments in microblogs by building adaptive sentiment lexicons. In the proposed method, corpora-based and lexicon-based approaches are combined and lexicons are generated from text. The sentiment classification is formulated as an optimization problem, in which the goal is to find optimum sentiment lexicons. A novel genetic algorithm is then proposed to solve this optimization pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 36 publications
0
49
0
5
Order By: Relevance
“…The various benchmark datasets used in the past decade were WePS-3, 27 SemEval, 30,52,54,55,73,75,76,85 tweets prepared by Stanford University, 34,45,46,75 SNAP, 40 Sanders Twitter Sentiment Corpus (denoted as Sanders), 44,55,75,79 2008 Presidential Debate Corpus, 44,75,79 Sentiment140, 51 RepLab 2012, 53 RepLab 2013, 53 STS-manual, 55 Gold Standard personality labeled Twitter dataset, 59 Cleveland Heart Disease data, 69 STS-Gold, 73 FIGURE 6 Distribution of papers in accordance to the digital libraries (expressed in percentages) Many reported researches were carried on the tweets fetched directly from Twitter using its API. The tweets were from a variety of domains, topics and time period (referred as topic specific/topic oriented tweets).…”
Section: • Widely Used Datasets and Domains In Which The Studies For mentioning
confidence: 99%
See 1 more Smart Citation
“…The various benchmark datasets used in the past decade were WePS-3, 27 SemEval, 30,52,54,55,73,75,76,85 tweets prepared by Stanford University, 34,45,46,75 SNAP, 40 Sanders Twitter Sentiment Corpus (denoted as Sanders), 44,55,75,79 2008 Presidential Debate Corpus, 44,75,79 Sentiment140, 51 RepLab 2012, 53 RepLab 2013, 53 STS-manual, 55 Gold Standard personality labeled Twitter dataset, 59 Cleveland Heart Disease data, 69 STS-Gold, 73 FIGURE 6 Distribution of papers in accordance to the digital libraries (expressed in percentages) Many reported researches were carried on the tweets fetched directly from Twitter using its API. The tweets were from a variety of domains, topics and time period (referred as topic specific/topic oriented tweets).…”
Section: • Widely Used Datasets and Domains In Which The Studies For mentioning
confidence: 99%
“…The tweets were from a variety of domains, topics and time period (referred as topic specific/topic oriented tweets). These prominently included tweets from or about elite personalities like actors; singers; sportsperson; comedians; politicians, authors, idols; entertainers, 28,34,37,40,54,55,67,70,73,75,79 etc, news and commemoratives, 17,30,48,58,59,64,67,79 health and fitness, 31,56,57,69,74,75,78,79 stock market exchanges, 29,34,63,82 companies like AT&T; Amazon;…”
Section: • Widely Used Datasets and Domains In Which The Studies For mentioning
confidence: 99%
“…A methodology proposed for corpus and lexicon based approaches mainly is used to create the text documents. This approach is used for classifying sentiments and polarity [27]. A genetic algorithm is proposed for optimization problem and is used for finding lexicons in the opinionated text.…”
Section: Hybrid Based Approachesmentioning
confidence: 99%
“…An approach for sentiment classification in micro blogs is proposed. Genetic algorithm, sentiment lexicon, meta-level features, Bing Liu's lexicon and n-gram features are used in the framework [27]. It requires concentrating on creation of the lexicon to reduce the time-consuming and sentiment score in other domains.…”
Section: Open Issues and Research Gapsmentioning
confidence: 99%
“…Results of the research demonstrated that is improved efficiency of feature selection of classifiers in the classification of opinions. A novel GA was proposed by Keshavarz&Abadeh [13] in solving optimization issues and to find lexicon to classify text. Adaptive sentiment lexicons were generated through this algorithm and on its basis, which was used along with Bing Liu's lexicon and ngram features.…”
Section: Related Workmentioning
confidence: 99%